Prolonged post-androgen abuse hypogonadism: potential mechanisms and a proposed standardized diagnosis - van Os, Joël; Smit, Diederik Laurens; Bond, Peter; de Ronde, Willem (Frontiers in Endocrinology, 2025)
Androgen abuse, which is increasingly prevalent, inevitably leads to suppression of the hypothalamic-pituitary-gonadal axis (HPGA). While most individuals recover HPGA function following androgen cessation, a subset experiences prolonged hypogonadism, with symptoms persisting for months or even years. Currently, this condition lacks a standardized definition, complicating both diagnosis and treatment. In this article, we explore the potential mechanisms underlying prolonged hypogonadism after androgen abuse, including the role of prolonged androgen activity, hypothalamic-pituitary alterations, testicular changes, suppression of sex hormone-binding globulin (SHBG), genetic predisposition, and undisclosed ongoing androgen abuse. We propose the term ‘Prolonged Post-Androgen Abuse Hypogonadism’(PPAAH) to standardize diagnosis and guide future research. PPAAH is provisionally defined as persistent hypogonadism six months after cessation of androgen abuse, in individuals with a cumulative androgen exposure of at least 150 mg per week for a minimum of six months. Diagnosing PPAAH requires excluding other causes of hypogonadism. This preliminary framework is intended to support further research into the pathophysiology and management of this condition, and may require refinement as further evidence emerges.